Effect of single water adsorption on the bond order of calcium silicates and its implication for hydration variation. Issue 5 (24th January 2022) - Qi, Chongchong; Xu, Xinhang; Wu, Mengting; Chen, Qiusong
Abstract: The differences in hydration between β‐C2 S and M3‐C3 S, the main phases of silicate cement, have not been fully investigated. In this study, density functional theory calculations were used to investigate the structure and bond order of β‐C2 S and M3‐C3 S before and after the molecular and dissociative adsorption of single water atoms. The unit cell of M3‐C3 S was found to have some O atoms with lower bond orders than those in β‐C2 S, implying higher chemical reactivity of O atoms in M3‐C3 S. The total bond orders of water atoms generally decreased after molecular adsorption, but reductions were minimal, and there were even increases, when the hydrogen bonding among H and surface O atoms was very weak in several M3‐C3 S surfaces. In the case of dissociative adsorption, the bond orders of water O–H hydroxyl tended to increase, and the other bond orders among water atoms decreased sharply, even to zero in some cases. Moreover, the bond order variations of water atoms of β‐C2 S and M3‐C3 S in molecular adsorption were highly correlated with the adsorption energy, with correlation coefficients of 0.9070 and 0.8330, respectively. In both molecular and dissociative adsorption of β‐C2 S and M3‐C3 S, the total bond order among Ca atoms with other surface atoms decreased after the Ca atoms adsorbed water atoms. This phenomenon also appeared in the dissociative adsorption of surface O atoms. In M3‐C3 S, the total strength of the surface O atom bonded to other surface atoms after dissociative adsorption was similar to the strength of the surface O–H hydroxyl bond. The special O atoms in M3‐C3 S showed a clear layered arrangement on the surfaces. In the case of dissociative adsorption, H atoms were preferentially adsorbed to special O atoms in the surface layer. Abstract : Single water adsorption on the calcium silicate.